Election in the digital period: a literature review - Rahmanto, Syam (Universitas Islam Malang, 2022)
The discourses to hold electronic elections or E-Voting also emerged in Indonesia. Several public figures stated that Indonesia needed to hold electronic elections. Before deciding to implement E-Voting, it is necessary to consider various aspects to maintain election principles. This article reviewed the implementation of elections in India, Estonia, Canada, and Brazil that have implemented E-Voting. The research method in this research was a literature review. The analysis results showed that India and Brazil used an E-Voting system with a machine or a DRE system. Estonia and Canada used the internet or I-Voting system. Public trust needed to be considered based on the four countries implementing E-Voting. Network stability, access to digital voters, and ease of access were obstacles that Estonia and Canada faced in implementing the I-Voting system. Voter participation, engine performance, and power grids were obstacles that India and Brazil faced in implementing the DRE system. Based on experiences from India, Brazil, Estonia, and Canada, Indonesia must design specific strategies to minimize the risk of implementing E-Voting in elections. Therefore, the advice that can be given is that the implementation of E-Voting can be started in stages and accompanied by efforts to equalize digital infrastructure in various regions and digital education in the community.